2011
DOI: 10.1097/opx.0b013e318205a18f
|View full text |Cite
|
Sign up to set email alerts
|

Goji Berry Effects on Macular Characteristics and Plasma Antioxidant Levels

Abstract: Overall, daily dietary supplementation with goji berry for 90 days increases plasma zeaxanthin and antioxidant levels as well as protects from hypopigmentation and soft drusen accumulation in the macula of elderly subjects. However, the mechanism of action is unclear, given the lack of relationship between change in plasma zeaxanthin and change in macular characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 20 publications
2
35
0
3
Order By: Relevance
“…Individuals in the S group included 14 g of in natura GB on meals. The choice of the amount of GB administered was based on a previous study conducted by Bucheli et al [28] in volunteers between 65 and 70 years. In that study, Bucheli et al showed positive effects in the use of GB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals in the S group included 14 g of in natura GB on meals. The choice of the amount of GB administered was based on a previous study conducted by Bucheli et al [28] in volunteers between 65 and 70 years. In that study, Bucheli et al showed positive effects in the use of GB.…”
Section: Methodsmentioning
confidence: 99%
“…Lycium barbarum , a traditional Chinese medicine plant, is a small red fruit widely consumed in China due to its benefits to vision, kidney, liver, and diseases such as diabetes mellitus and obesity [19]. It is considered the richest natural source of antioxidants vitamin C, flavonoids, and carotenoids especially zeaxanthin, quercetin, and rutin [2022].…”
Section: Introductionmentioning
confidence: 99%
“…A mouse consumes ;3 g/d of diet, which translates into a daily consumption of wolfberry at 5 g/kg body weight for a mouse weighing 30 g. When this dose is converted from mice consuming 12 kJ/d to humans consuming 2000 kJ/d, using isocaloric calculation (51,52), it is equivalent to 0.18 g/kg body weight in humans, or 12.6 g/d consumed by a person weighing 70 kg. A recent study showed that the elderly subjects (aged 65-70 y) receiving 13.7 g/d of LWB for 3 mo had improved macular characteristics compared with the placebo group (50). Thus, the dose used in the current study is both feasible to be consumed by humans and could have translational potential.…”
Section: Discussionmentioning
confidence: 84%
“…Considering this, some experiments have investigated the therapeutic effect of the LBA on the visual defect. As LBA is one of the richest natural sources of ze axanthin [2], previous investigations found that daily dietary supplementation with LBA could increase plasma zeaxanthin and antioxidant levels as well as protects from hypopigmentation in the macula of elderly subjects [5]. In addition, oral administration of LBA could significantly reduce the loss of retinal ganglion cells in rats with glaucoma by decreasing the ocular hypertension [7].…”
Section: Introductionmentioning
confidence: 99%